Technical standards in allergen exposure chambers worldwide – an EAACI Task Force Report. Issue 12 (28th November 2021) - Pfaar, Oliver; Bergmann, Karl‐Christian; Bonini, Sergio; Compalati, Enrico; Domis, Nathalie; de Blay, Frédéric; de Kam, Pieter‐Jan; Devillier, Philippe; Durham, Stephen R.; Ellis, Anne K.; Gherasim, Alina; Haya, Laura; et al.
Abstract: Allergen exposure chambers (AECs) can be used for controlled exposure to allergenic and non‐allergenic airborne particles in an enclosed environment, in order to (i) characterize the pathological features of respiratory diseases and (ii) contribute to and accelerate the clinical development of pharmacological treatments and allergen immunotherapy for allergic disease of the respiratory tract (such as allergic rhinitis, allergic rhinoconjunctivitis, and allergic asthma). In the guidelines of the European Medicines Agency for the clinical development of products for allergen immunotherapy (AIT), the role of AECs in determining primary endpoints in dose‐finding Phase II trials is emphasized. Although methodologically insulated from the variability of natural pollen exposure, chamber models remain confined to supporting secondary, rather than primary, endpoints in Phase III registration trials. The need for further validation in comparison with field exposure is clearly mandated. On this basis, the European Academy of Allergy and Clinical Immunology (EAACI) initiated a Task Force in 2015 charged to gain a better understanding of how AECs can generate knowledge about respiratory allergies and can contribute to the clinical development of treatments. Researchers working with AECs worldwide were asked to provide technical information in eight sections: (i) dimensions and structure of the AEC, (ii) AEC staff, (iii) airflow, air processing, and operating conditions, (iv) particle dispersal, (v) pollen/particle counting, (vi) safety and non‐contamination measures, (vii) procedures for symptom assessments, (viii) tested allergens/substances and validation procedures. On this basis, a minimal set of technical requirements for AECs applied to the field of allergology is proposed. Abstract :